Escherichia Coli Brain Abscess in an Immunocompetent Adult: Case Report - R., El Fargani; M., Idalene; W., Ait Driss; N., Tassi (International Journal of Innovative Research in Medical Science, 2025)
Background: Escherichia coli (E. coli) is the main bacterium responsible for neonatal meningitis. Cases brain abscess and subdural empyema due to E. coli are extremely rare in immunocompetent adults. We present here the case of a patient with intravenous drug addiction as a risk factor, who developed an E. coli brain abscess following a simple urinary tract infection.